Aplicación hormonal enla germinación de sacha inchi (Plukenetia vulobilis L.) - Bustamante Castillo, Miguel Sebastian (2011)
Inchi Sacha is a promising crop for the conditions of the Ecuadorian Amazon mainly the province of Pastaza and Morona Santiago as an alternative for the solution to the lack of work there and also in promoting reforestation of deforested areas for agricultural activities forest that have been abandoned. This research work was carried out in the fifth experimental Cynthia, owned by Mr. Luis Cáceres, located in the province of Pastaza, Canton Pastaza Parish Tarqui, whose location is, Latitude 1 ° 31 '0''South, Longitude 77 º 59' 25''West, at a height of 889 m Lasted 90 days and had as main objective to verify the action of the hormone NAA (naphthalene acetic acid) on germination of seeds of Sacha Inchi. The treatments were: 50, 100, 150, 250, 500, 750, 1000, 1500, 2000 mg of ANA + a witness. DCA design was used, with 8-plant plots with three replications, giving a total of 240 plants. The objects of study variables were: number of germinated plants per experimental unit. Stem diameter in inches, height of plants, number of leaves per plant, root mass, root number and the corresponding economic analysis. The results: The tallest plants were obtained with 100 mg of ANA. The best root weight and leaf number is registered with the concentration of 750 mg NAA. The highest root length was reported with 1500 mg of ANA. Number of roots and leaves weight of the highest values obtained with 2000 mg of ANA. The control treatment had the highest weight of stems. To stem diameter higher values are registered with the concentration of 50 and 1500 mg of ANA. The best cost / benefit ratio is obtained with 50 and 100 mg of ANA